Quem entra e quem fica de fora? : ônus administrativos e reprodução de desigualdades na implementação dos editais da Lei Aldir Blanc (LAB) : um estudo de caso em Minas Gerais - Lucas Melo Franco Fainblat (2024)
This dissertation investigates whether the calls for proposals under the Aldir Blanc Law (LAB) executed in 2020 in Minas Gerais (MG) reproduced inequalities (Pires, 2019) through administrative burdens (Burden; Canon; Mayer; Moynihan, 2012), exploring how they constitute access barriers that hinder the success of projects by individuals and micro-entrepreneurs. A comparison of 9,871 projects submitted to the LAB calls was conducted using binomial logistic regression models based on data from the LAB Calls Execution Report (Minas Gerais, 2022). Variables such as educational level, age group, race, gender, and geographic location were considered to measure variations in the incidence of social exclusion mechanisms (Kidd, 2017) that could increase informational, compliance, and psychological costs (Herd; Moynihan, 2020) associated with overcoming administrative burdens. The findings demonstrate the reproduction of inequalities within the scope of the LAB calls, despite the considerable positive advancements the policy has made in reducing access barriers. Under ceteris paribus conditions, projects by individuals with low education levels had up to 50% lower chances compared to those with higher education levels (depending on the interaction between education, race, and gender). All else being equal, projects by non-white individuals (black, brown, yellow, and indigenous) had a 17% lower chance of success compared to white individuals. The research contributes new perspectives on the reproduction of inequalities in cultural policies, focusing on their instrumentation (Lascoumes; Le Galès, 2007) and providing evidence that administrative burdens significantly hinder access for vulnerable social groups.